2020
DOI: 10.3389/fpsyt.2020.00078
|View full text |Cite
|
Sign up to set email alerts
|

Active Ingredients and Mechanisms of Change in Motivational Interviewing for Medication Adherence. A Mixed Methods Study of Patient-Therapist Interaction in Patients With Schizophrenia

Abstract: Background: Trials studying Motivational Interviewing (MI) to improve medication adherence in patients with schizophrenia showed mixed results. Moreover, it is unknown which active MI-ingredients are associated with mechanisms of change in patients with schizophrenia. To enhance the effect of MI for patients with schizophrenia, we studied MI's active ingredients and its working mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The mechanisms of change "arguing oneself into change" and "changing self-perceptions" were not tested in this study (Magill et al, 2017). In our previous qualitative study on active ingredients and mechanisms of change in motivational interviewing for medication adherence in a population of patients with schizophrenia (Dobber et al, 2020), we found many clues for the mechanisms of change "arguing oneself into change, " a few for "increasing motivation to change" and one clue for "changing self-perception, " but no clues for "increasing self-efficacy/confidence." It is plausible that self-efficacy plays a more important role in decreasing alcohol use and in smoking cessation than in medication adherence.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The mechanisms of change "arguing oneself into change" and "changing self-perceptions" were not tested in this study (Magill et al, 2017). In our previous qualitative study on active ingredients and mechanisms of change in motivational interviewing for medication adherence in a population of patients with schizophrenia (Dobber et al, 2020), we found many clues for the mechanisms of change "arguing oneself into change, " a few for "increasing motivation to change" and one clue for "changing self-perception, " but no clues for "increasing self-efficacy/confidence." It is plausible that self-efficacy plays a more important role in decreasing alcohol use and in smoking cessation than in medication adherence.…”
Section: Discussionmentioning
confidence: 95%
“…oneself into change") (Bem, 1967;Miller, 1983;Gollwitzer, 1999;Miller and Rollnick, 2002, 2004McNally et al, 2005;Moos, 2007;Arkowitz et al, 2008;Gaume et al, 2008;Apodaca and Longabaugh, 2009;Miller and Rose, 2009;Barnett et al, 2010;Glynn and Moyers, 2010;Lee et al, 2010;Berger and Villaume, 2013;Moyers and Miller, 2013;Apodaca et al, 2014;Berger and Bertram, 2015;Copeland et al, 2015;Magill et al, 2015Magill et al, , 2018. In a previous study (Dobber et al, 2020), we performed a systematic literature search for active ingredients and mechanisms of change in PsychInfo, in PubMed, and in textbooks on MI. Based on the research (Gollwitzer, 1999;McNally et al, 2005;Gaume et al, 2008;Apodaca and Longabaugh, 2009;Barnett et al, 2010;Glynn and Moyers, 2010;Lee et al, 2010;Apodaca et al, 2014;Copeland et al, 2015;Magill et al, 2018) and MI theory (Bem, 1967;Miller, 1983;Gollwitzer, 1999;Miller and Rollnick, 2002, 2004McNally et al, 2005;Moos, 2007;Arkowitz et al, 2008;…”
Section: Client Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this literature review, we searched some studies putting a strong emphasis on certain physician interventions leading to improved medication adherence. Motivational interviewing (MI) is one of the most important physician factors in improving medication adherence [30][31][32][33]. A trusting relationship and empathy enable both the physician and the patient to attain depth in the conversation and this fruitful interaction gives opportunities to trigger mechanisms of change of behavior in the patient toward adherence.…”
Section: Schizophreniamentioning
confidence: 99%